(3OQGSI aj Xd GdfTQI Qbe (B600s - (3UHQjfI(B, (3MHIs ((3GdLRGFQ(B:s (3OGQ gheI ddWHGYI hGdfTQ hGdJhRjY(B,s, 2018)
(3GdCYQGa GdJLGQjI GdOhdjI hGdGYJeGO GdeSJfOj, eY WHjYI gPG GdCNjQ hJUfjaGJg, HGdGVGaI Gdi GdCMcGe GdfGTFI Yf aJM hJfajP GdGYJeGO GdeSJfOj GdbWYj, hGdYdGbI GdbGFeI Hjf GdeUQa hGdYejd GdBeQeY GdJRGe GdeUQa aj ehGLgI GdYejd GdBeQ, h aMU GdeSJfOGJ HeYjGQ Jbfj, eY JYOjd eOI GdaMU, heSDhdjI GdeUQa aj MGdI GdZT hShAfjI GdeSJajO(B. s
(3eQGLY U(B.157s
Keywords: (3GdGYJeGOGJ GdeSJfOjIs; (3GdHfhcs; (3GdJLGQI GdOhdjIs